Penguatan Keterampilan Digital Guru Melalui Pelatihan Wordwall di SDN 205/IV Kota Jambi: Pengabdian - Desy Rosmalinda; Syarif, Ahmad; Risdalina; Issaura Sherly Pamela; Erlinda Amnie; Louisiana Muliawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In the rapidly evolving digital era, the need for digital integration in teacher learning is becoming increasingly urgent. Teachers are no longer the primary source of knowledge, but rather managers and sophisticated instructors in the use of technology such as wordwalls in a more effective, efficient, and interactive learning process. Wordwall training is an alternative in efforts to improve the quality of teacher learning, especially in Jambi City. This Wordwall training was conducted at SDN 205/IV Jambi City, which had 53 teachers. Based on teacher experience data, the results obtained were a satisfaction level increase of 40% of participants feeling